Pengaruh Kompetensi Sumber Daya Manusia, Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Desa: Studi Kasus Kec. Kabila Bone Kab. Bone Bolango - Anjelina Yuli Ratnasari; Usman; Andi Yusniar Mendo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to determine the influence of human resource competence, accounting information systems, and internal control systems on the quality of village financial reports in Kabila Bone District, Bone Bolango Regency. The type of method used in this research is a quantitative method with data collection techniques using questionnaire surveys and observation. The number of respondents in this research was 63 respondents consisting of the Village Head, Village Secretary, Village Treasurer, Head of Planning, Head of Government, Head of Welfare and Services, and Chair of the Village Consultative Body (BPD) throughout Kabila Bone District. The tool used in this research uses multiple linear regression analysis. The research results show that 1. Human resource competency has a positive and significant effect on the quality of village financial reports in Kabila Bone District. 2. The accounting information system has a positive and significant effect on the quality of village financial reports in Kabila Bone District. 3. The internal control system has a positive and significant effect on the quality of village financial reports in Kabila Bone District. 4. Simultaneously, human resource competency, accounting information systems and internal control systems have a positive effect on the quality of village financial reports in Kabila Bone District with a determinant value of 60.6% while the remaining 39.4% is explained by other variables not examined. in this research.